A perfectionist basic structure. (September 2019) - Ferdman, Avigail
When philosophers talk about perfectionism, it is usually as a view of well-being, of developing characteristically human capacities. Yet perfectionism can also be a normative account of what we owe to each other. This article argues that perfectionists have reason to endorse a perfectionist basic structure such that enables persons to develop and exercise their human capacities in meaningful ways. This basic structure has two complementary features: First, it enables a diversity of life experiences. Second, it provides a spatial opportunity structure that creates open-minded environments. Absent these features, rich or lucky individuals gain an unfair advantage in the sphere of opportunities for developing their capacities in meaningful ways.